Prospective elementary school teachers perceptions on the use of technology in natural science learning - Annisa, Nurul; Rikayana, Askha Egyta; Cahyo, Septian Dwi; Pambudi, Sulistyo; Wijayanti, Mia; Yuniarti, Yeni; Zayadi, Nur Hidayah Binti; Adlawan, Hendely A.; Sukardi, Rendi Restiana (Education and Development Research, 2023)
Technology nowadays has undergone continuous innovation, and its use has grown considerably in society. One form of integration of technology into learning is through natural science learning. Studies on perception of prospective elementary school teachers on the use of technology in natural science learning is still under-research. Thus, this research aims to unravel perceptions and preparations of prospective elementary school teachers for the use of technology in natural science learning and how such perceptions and preparations can influence how natural science learning will be implemented in the future. This research used a descriptive method, and data collection was carried out via a questionnaire. The subjects of research were students of the 5th semester and higher during the odd semester of the academic year 2022/2023 of PGSD Study Program at Universitas Negeri as prospective elementary school teachers. It can be concluded that the prospective elementary school teachers have a good perception of the use of technology in natural science learning. The perceptions discussed include knowledge about technology, knowledge about learning science, experience using technology in learning, the factor of the necessity of using technology in learning science, the benefits of technology in learning science, and types of technology that are appropriate for learning science.